TANGGUNG JAWAB (HUKUM) PERAWAT DALAM MELAKSANAKAN PRAKTEK KEPERAWATAN MANDIRI DITINJAU DARI ASPEK HUKUM ADMINISTRASI - Galang Asmara (Perspektif, 2005)
The carry out nurse of nursing as professionalism, Nowadays has the position the same as with doctor. That could be seem from practices licenses of nurse like doctors. But there are have consequently nurse must be responsible and liable for their erroneous. This article will be study about responsibility of nurse from perspective of administrative law The study using normative approach. As result of this study nurse could be responsible from three legal aspect is private law, criminal law and administrative law Administrative law perspective is a nurse that given administrative punishment like cancel their license if they make mistaken in their practice of the profession. The legal protection for nurse, is organization of nurse must be make professionalism standard as measurement of professional nursing practices. Beside that, the government must be made council for health workers discipline (Disiplin Tenaga Kesehatan) as institution have authority to given punishment to a nurse who carry out wrong practice.